2004
DOI: 10.1007/s10228-004-0242-6
|View full text |Cite
|
Sign up to set email alerts
|

Territorial defense against various food competitors in the Tanganyikan benthophagous cichlid Neolamprologus tetracanthus

Abstract: Territorial defense of nonbreeding female Neolamprologus tetracanthus, a shrimp-eating Tanganyikan cichlid, was investigated. Females defended territories (ϭhome ranges, ca. 1 m across) against a variety of intruding fishes. Conspecific females were usually attacked outside the territories, heterospecific benthivores (shrimp eaters) and omnivores near the border of the territories, and piscivores, algae and detritus feeders, and herbivores inside the territories. Females used some parts of the sandy substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Fish species also show forms of resource defence. The cichlid, Neolamprologus tetracanthus, for example, defends a territory containing food resources against intra-and interspecific food competitors (Matsumoto and Kohda 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Fish species also show forms of resource defence. The cichlid, Neolamprologus tetracanthus, for example, defends a territory containing food resources against intra-and interspecific food competitors (Matsumoto and Kohda 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Both sexes of this fish feed on shrimps on the lake bottom (M. Hori, 1990, personal communication). Inside large territories of males, females maintain small feeding territories against many food competitors (Matsumoto and Kohda 1998Kohda , 2004. During field observations, we noticed that haremic males appeared to avoid foraging inside female territories, although they frequently entered the territories.…”
Section: Introductionmentioning
confidence: 96%
“…Intraspecific behavioral studies have shown that H. cyanoguttatus are aggressive as invaders and as residents (Turner 1994;Draud et al 2004;Leiser et al 2004), and that L. macrochirus are aggressive as territory-holding adult males (Colgan et al 1978). Relatively few studies have examined interspecific aggression within these families (Colgan and Gross 1977;Matsumoto and Kohda 2004), and cichlid-centrarchid interactions have only rarely been studied (e.g., Brooks and Jordan 2009). Such a study could demonstrate behavioral effects of invasive species and better explain success of non-native fishes in the wild.…”
Section: Introductionmentioning
confidence: 97%
“…We also conducted similar observations (though with fewer trials) on interactions between H. cyanoguttatus and native redspotted sunfish (L. miniatus), a particularly aggressive native centrarchid (personal observation). In general, most species of the families Cichlidae and Centrarchidae are considered aggressive freshwater fishes, with members of both groups employing aggression in interspecific and intraspecific interactions (Marchetti 1999;Matsumoto and Kohda 2004). Intraspecific behavioral studies have shown that H. cyanoguttatus are aggressive as invaders and as residents (Turner 1994;Draud et al 2004;Leiser et al 2004), and that L. macrochirus are aggressive as territory-holding adult males (Colgan et al 1978).…”
Section: Introductionmentioning
confidence: 98%